A retrial queueing system with processor sharing and impatient customers - V. I. Klimenok (Informatika)
Objectives. The problem of constructing and investigating a mathematical model of a stochastic system with processor sharing, repeated calls, and customer impatience is considered. This system is formalized in the form of a queueing system. The operation of the queue is described in terms of multi-dimensional Markov chain. A condition for the existence of a stationary distribution is found, and algorithms for calculating the stationary distribution and stationary performance characteristics of the system are proposed.Methods. Methods of probability theory, queueing theory and matrix theory are used.Results. The steady state operation of a queueing system with repeated calls, processor sharing and two types of customers arriving in a marked Markovian arrival process is studied. The channel bandwidth is divided between two types of customers in a certain proportion, and the number of customers of each type simultaneously located on the server is limited. Customers of one of the types that have made all the channels assigned to them busy leave the system unserved with some probability and, with an additional probability, go to the orbit of infinite size, from where they make attempts to get service at random time intervals. Customers of the second type, which caused all the channels assigned to them to be busy, are lost. Customers in orbit show impatience: each of them can leave orbit forever if the time of its stay in orbit exceeds some random time distributed according to an exponential law. Service times of customers of different types are distributed according to the phase law with different parameters. The operation of the system is described in terms of a multi-dimensional Markov chain. It is proved that for any values of the system parameters this chain has a stationary distribution. Algorithms for calculating the stationary distribution and a number of performance measures of the system are proposed. The results of the study can be used to simulate the operation of a fixed capacity cell in a wireless cellular communication network and other real systems operating in the processor sharing mode.